Evaluation of polyol‐made Gd3+‐substituted Co0.6Zn0.4Fe2O4 nanoparticles as high magnetization MRI negative contrast agents. Issue 1 (18th February 2019) - Mnasri, Walid; Bentahar, Lotfi; Nowak, Sophie; Sandre, Olivier; Boissière, Michel; Ammar, Souad
Abstract: The structural, microstructural, and magnetic properties of ~5‐nm‐sized Co0.6 Zn0.4 Fe2 −  x Gd x O4 nanoparticles were investigated in order to evaluate their capability to enhance the magnetic resonance imaging contrast as high magnetization agents. A focus was made on the solubility of Gd 3+ cations within the spinel lattice. By coupling X‐ray diffraction to X‐ray fluorescence spectroscopy, we demonstrated that only a limited fraction of Gd 3+ can substitute Fe 3+ ions into the whole crystal structure and does not exceed 6 at.‐%. At this concentration, the room temperature (27°C) saturation magnetizations of the prepared superparamagnetic nanocrystals were found to be close to 80 emu g −1 . Coating these nanoparticles with hydrophilic dopamine ligands leads to the formation of ~50‐nm‐sized clusters in water. As a consequence, relatively high r 2 / r 1 ratios of transverse to longitudinal proton relaxivities and high r 2 values were measured in the resulting colloids at physiological temperature (37°C) for an applied magnetic field of 1.41 T: 33 and 188 mM −1  sec −1, respectively, for the richest system in gadolinium. Moreover, after incubation with healthy human model cells (fibroblasts) at doses as high as 10 μg mL −1, they induce neither cellular death nor acute cellular damage making the engineered probes particularly valuable for negative magnetic resonance imaging contrasting. Abstract : High transversal relaxivity was measured on highly magnetized ferrite‐based negative contrast agents prepared by the polyol process. They consisted of zinc and gadolinium‐substituted 5‐nm‐sized cobalt ferrite particles, functionalized by hydrophilic catechol ligand.